The seasonally dry tropical forest species Cavanillesia chicamochae has a middle Quaternary origin. (11th November 2021) - Bacon, Christine D.; Gutiérrez‐Pinto, Natalia; Flantua, Suzette; Castellanos Suárez, Diego; Jaramillo, Carlos; Pennington, R. Toby; Antonelli, Alexandre
Abstract: We use DNA sequence data to understand the evolutionary history of the genus Cavanillesia (Malvaceae), with particular emphasis on C . chicamochae, an emblematic succulent‐trunked tree endemic to seasonally dry tropical forests (SDTFs) of the Chicamocha Canyon of Colombia, South America. Based on field sampling of multiple individuals from different populations, we inferred a phylogeny calibrated into absolute time using robust macrofossil information. We show strong support for a monophyletic Cavanillesia chicamochae, with a mean stem age of 1.46 Ma. Two different mechanisms could explain its origin, either a late uplift age of the eastern cordillera or increased dryness of the Chicamocha Canyon during the Middle Pleistocene Transition. We also find marked genetic differentiation of its populations within the Chicamocha Canyon, likely driven by a combination of climate change and local landscape processes. Our results suggest that within northern inter‐Andean SDTFs, as has been demonstrated in the central Andes, dispersal limitation leads to species and even population monophyly within individual valleys. The genetic differentiation of populations of C . chicamochae, together with the presence of other endemic and threatened species in the Chicamocha Canyon, calls for urgent management to conserve the unique biodiversity in the region. Abstract in Spanish is available with online material. Abstract : We use DNA sequence data to understand the evolutionary history of the genus Cavanillesia (Malvaceae), with particular emphasis on C. chicamochae, an emblematic succulent‐trunked tree endemic to seasonally dry tropical forests (SDTFs) of the Chicamocha Canyon of Colombia, South America. The species originated in the Quaternary and the genetic differentiation of populations, together with the presence of other endemic and threatened species in the Chicamocha Canyon, call for urgent management to conserve the unique biodiversity in the region. Resumen: En este estudio, utilizamos datos moleculares (secuencias de ADN) para comprender la historia evolutiva del género Cavanillesia (Malvaceae), haciendo hincapié en C . chicamochae, un árbol emblemático de troncos suculentos, endémico de los bosques tropicales estacionalmente secos (BTES) del Cañón del Chicamocha de Colombia, América del Sur. Inferimos una filogenia calibrada en tiempo absoluto, en base al muestreo de campo de múltiples individuos de diferentes poblaciones y a la robusta información que proporcionan los macrofósiles. Los resultados filogenéticos indican que C . chicamochae forma un clado monofilético de Cavanillesia, cuya edad media es de 1.46 Ma. Su origen podría explicarse por dos mecanismos diferentes: ya sea por un levantamiento tardío de la cordillera oriental; o por unas mayores condiciones áridas del Cañón del Chicamocha durante la Transición del Pleistoceno Medio. Además, encontramos una marcada diferenciación genética de sus poblaciones dentro del Cañón del Chicamocha, probablemente impulsada por una combinación de efectos debidos al cambio climático y procesos propios del paisaje local. Nuestros resultados sugieren que dentro de los BTES interandinos del norte, la limitación de la dispersión conduce a la formación de especies e incluso a poblaciones monofiléticas dentro de los valles individuales, como ya se ha demostrado en los Andes centrales. La diferenciación genética de las poblaciones de C . chicamochae, junto con la presencia de otras especies endémicas y amenazadas en el Cañón del Chicamocha, exigen una gestión urgente para conservar la biodiversidad única de esta región.